Pengaruh Konsentrasi dan Frekuensi Penyiraman Fitohormon Organik terhadap Pertumbuhan dan Hasil Bawang Merah (Allium ascalonicum L.) - Yanerius Amsikan (Savana Cendana, 2021)
This study aims to determine the effect of organic phytohormone administration on the growth and yield of shallots. Getting the best dose and frequency of organic phytohormone on the growth and yield of onions. This study used a Randomized Block Design (RBD), with a factorial pattern of 3 x 3. The first treatment was the concentration of organic matter (Y) with 3 levels, namely concentration (Y0), the concentration of 45 ml / l of water (Y1), and concentration of 90 ml / l water (Y2) and the second treatment is watering frequency (G) which consists of 3 levels, namely 1 week (G1), 2 weeks (G2), and 3 weeks (G3) The results of the study showed that there was no interaction between the combination of phytohormone dose treatment and frequency of phytohormone watering. Phytohormone dose treatment of 90 ml / l and frequency of watering once a week had a very significant effect on the observation of total plant fresh weight. The phytohormone 45 dose treatment did not significantly affect the treatment but the average showed the best plant growth.